2022
DOI: 10.31234/osf.io/pfzkh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploratory Graph Analysis in context

Abstract: The current paper presents the network psychometric framework for dimensionality and item analysis termed exploratory graph analysis (EGA). It starts by briefly contextualizing the field of network psychometrics and the early work from the 50’s and 60’s. Then it provides a brief overview of exploratory graph analysis and other recent developments, such as the network loadings (a metric akin to factor loadings), total entropy fit index (verification of dimensionality fit), dynamic EGA, bootstrap EGA for dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Data were analyzed using SPSS Version 27 software and the R/ EGA package. 20,21 Summed scores were used in correlations between MLQ 5X leadership styles and HI communication clusters. Skewness and kurtosis of the summed scores were in the range of normality, and Pearson correlations were used to evaluate the strength and direction of the summed scores.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using SPSS Version 27 software and the R/ EGA package. 20,21 Summed scores were used in correlations between MLQ 5X leadership styles and HI communication clusters. Skewness and kurtosis of the summed scores were in the range of normality, and Pearson correlations were used to evaluate the strength and direction of the summed scores.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted data analysis using SPSS v. 26 (IBM Corp, 2019) and R (R Core Team, 2021), employing the following R packages: "foreign" (0.8-84; R Core Team, 2022), "lavaan" (v0.6-12; Rosseel, 2012), "psych" (v2.2.9; Revelle, 2022), "EFAtools" (v0.4.4; Steiner, 2023), "EGAnet" (v1.1.1, Golino & Christensen, 2022), "semTools" (v0.5-6; Jorgensen et al, 2020), "ggpubr" (v0.6.0; Kassambara, 2023a), "rstatix" (v0.7.2; Kassambara, 2023b), "car" (v3.1-2, Fox et al, 2023), "responsePatterns (v0.1.0; Rihacek & Gotfried, 2022), and "emmeans" (v1.8.6;Lenth, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A recent advancement in network psychometrics is exploratory graph analysis (EGA). [15][16][17] EGAworks by first modeling the correlation matrix of the observable variables and then using the graphical least absolute shrinkage and selection operator (LASSO) regularization to gain a sparse inverse covariance matrix (Gaussian graphical model). Next, the Walktrap cluster detection algorithm 18 -a common technique for estimating clusters in weighted networks-identifies a discrete number of dense subgraphs (ie, clusters or communities) of the partial correlation matrix calculated in the previous step.…”
Section: Exploratory Graph Analysismentioning
confidence: 99%
“…In other words, as partial correlations are used in estimating network models, the use of the L1 regularization technique is important in controlling spurious/insignificant connection links between variables. 19 Indeed, 2 recent simulation studies 15,19 demonstrated that EGA achieves the overall highest accuracy compared with a number of traditional factor analytics including scree test and parallel analysis. Golino et al 16 also reported that EGA shows the highest overall accuracy (87.9%) in detecting the number of simulated dimensions, which is followed by the traditional parallel analysis with principal components (83.0%) and parallel analysis using principal axis factoring (81.9%).…”
Section: Exploratory Graph Analysismentioning
confidence: 99%
See 1 more Smart Citation